DETERMINATION OF FABRICS COLOR FASTNESS, SWEAT RESISTANCE AND COLOR FADING RESISTANCE (Scientific journal of the Fergana State University, 2024)
According to the research results, it was shown that the determined properties of silk fabrics are significantly higher than those of other fabrics. These fabrics have been shown to be used by humans in a variety of applications.